Problematika Pengajuan Permohonan Di Mahkamah-Konstitusi - Bambang Sutiyoso (Fakultas Hukum Universitas Islam Indonesia, 2006)
Society andjusticiabellen whose rights and constitutional authority are disadvantaged can defend their rights by requesting to the Constitutional Court. The problem raises because there is not clear regulation in the mechanism of requesting to the Constitutional Court, especially on the procedural law. In order the request isnot dismissed by the Constitutional Court, is should be estabilised the regulation relates to the case.